Escherichia coli mutants deficient in guanine-xanthine phosphoribosyltransferase. - Holden, J A (1976)
We studied the purine phosphoribosyltransferases (PRTases) of Escherichia coli and were able to isolate a mutant that is defective in its ability to convert guanine and xanthine to their respective ribonucleotides. The affected gene (gpt) lies between metD and proA and is 78.6% co-transducible with proA. Both this point mutant and a strain with a pro-lac deletion contain less than 2% of wild-type xanthine PRTase activity, yet still contain about 30% of wild-type guanine PRTase activity. Thus, the gpt gene is only one of at least two genes responsible for guanine PRTase activity in E. coli.